Motivating children with specific learning difficulties a teacher's practical guide - Elbeheri, Gad; Reid, Gavin 1950-; Everatt, John (London Routledge, 2018)
'Motivating Children with Specific Learning Difficulties' provides a comprehensive and definitive guide to what teachers need to know about motivation in pupils with specific learning difficulties, including dyslexia, dyspraxia and ADHD.
Machine generated contents note: 1. Specific learning difficulties (SpLDs) in context: Research to practice -- Education and motivation -- Researching motivation -- Learning and motivation -- Learning difficulties and motivation -- Overview of book chapters -- 2. The process of motivation -- The meaning of motivation -- Types of motivation -- Intrinsic motivation -- Extrinsic motivation -- Motivation, values, interests and goals -- Self-motivation -- Sources and assessment of motivation -- 3. Theories of motivation -- Reinforcement theory -- Moslem's hierarchy of needs -- Alderfer's ERG theory -- McClelland's need for achievement theory -- Locus of control theory -- Keller's ARCS model of motivational design -- Self-determination theory -- Vroom's expectancy theory of motivation -- Characteristics of motivation -- Domain-specific motivation -- Motivation and gender -- Motivation, achievement and IQ -- Motivation and age -- Motivation and rewards -- 4. Factors of motivation -- Motivating factors -- Teachers' personal qualities -- Teachers' teaching methods -- Quality of feedback -- Classroom management -- Methods of assessment -- Task difficulty level -- Students' beliefs and attitudes -- Extracurricular activities -- Impacting motivation in the classroom -- 5. Motivating students with reading difficulties -- Motivation and reading -- The role of self-esteem -- Achievement and motivation -- The importance of early intervention -- The role of rewards in reading -- Dyslexia -- Reading difficulties -- Key factors in reading -- Learning strategies and motivation -- Developing metacognition -- Encourage self-questioning -- Comprehension monitoring -- Activate prior knowledge -- Visual imagery -- Meaningful experiences -- Reciprocal teaching -- Scaffolding -- Encourage the use of self-assessment -- Supports leading to motivation -- Motivating readers -- Differentiated texts -- Paired reading -- Other motivational strategies -- Set goals -- Give feedback -- Opportunities to develop self-monitoring and self-assessment -- Conclusion -- 6. Motivating students with writing difficulties -- Spelling difficulties -- Spelling strategies and motivation -- Word lists -- Visual strategies -- Simultaneous oral spelling -- Spelling materials -- The writing process -- Handwriting -- some points to consider -- Dysgraphia -- Pre-writing activities -- A structure for writing -- Essay-writing skills/stages -- Stage 1 Collection of information -- Stage 2 Planning -- Stage 3 Essay writing -- Stage 4 Proofreading -- Ensuring motivation: Some key points -- Providing feedback: Three types of feedback -- 1. Monitoring -- 2. Constructive -- 3. Negative -- Developing independence -- Concluding comments -- 7. Motivating students with mathematics difficulties -- Definition -- Overlaps with dyslexia -- Motivation through identification -- Intervention -- Assessing maths difficulties to target motivational strategies -- Understanding motivation and maths -- Some concluding points -- 8. Motivating students with motor coordination difficulties -- Interventions related to motor development -- Characteristics and interventions associated with dyspraxia -- School ethos and children with motor coordination difficulties -- Concluding comments -- 9. Motivating students with attention, emotional and behavioural difficulties -- ADHD/EBD -- Learning, environment and motivation -- Medication, psychosocial interventions and motivation -- Conclusions -- 10. Motivation and self-concept -- Motivation, self-esteem and self-appraisal S9 Motivation and resilience -- Interventions: Academic and psychosocial development -- Individual and developmental differences -- Conclusion -- 11. Motivation and the role of assistive technology -- Customisation -- Interactive video and literacy games -- Interactive technology and social media -- Concluding comments -- 12. Motivation and the role of school and family -- Introduction -- Quality versus quantity of parental involvement -- Characteristics of parents and motivation -- Parents' perceived competence -- Parents' attitudes and beliefs towards school -- Parents' house rules -- School targeted motivation programmes -- Extracurricular activities and motivation -- 13. Conclusions and reflections -- An overview framework -- Motivation differences -- Importance of school ethos -- Value motivation -- Learning-rich environment -- Value the individual -- Celebrate success -- Appreciate differences -- Student space -- At ease with the environment -- Social learning -- Group approaches -- friendships -- Collaborate -- Collaborate with parents and the whole community -- Ability to access the learning materials -- Expectations and goals -- What is realistic? -- Reflection -- Feedback -- SpLDs and motivation -- Early intervention -- Individual and whole-person approaches -- Teachers and team work -- Learning strategies -- Teacher motivation.
Cover title: A teacher's practical guide : motivating children with specific learning difficulties.
Includes bibliographical references.
Keywords: Learning disabled children -- Education; Learning disabled children -- Psychology; Motivation in education